Assessment of Polycyclic Aromatic Hydrocarbons and Heavy Metal Pollutants in Soil Around Semi Urban Petrol Stations and Automobile Mechanic Workshops - Sikakwe, Gregory Udie; Tyopine, Andrew Aondoaver; Eyong, God'swill Abam (UI Scholars Hub, 2022)
This study assessed the heavy metals and polycyclic aromatic hydrocarbons (PAHs) pollutant in soil around petrol filling stations and automobile mechanic workshops. Samples of soil were acquired from the depth range of 0–15 cm. Toxic heavy metals were analyzed with atomic absorption spectrophotometry. The PAHs were analyzed using phytochemical chromatographic analysis by the Soxhlet extraction method. The soil tested was weakly acidic (6.12–6.81). The trend of the heavy metals’ mean levels in soil followed the order: lead (Pb) > nickel (Ni) > vanadium (V) > cadmium (Cd). The mean levels of PAHs were in the order: 1,2-benzanthracene pyrene > anthracene > fluorene > benzo(b)fluoranthene > 1,1,2-benzopyrelene (BghiP) > naphthalene (Naph) > Dibenz(a, h)anthracene > 1, 2 benzanthracene > benzo(k)fluoranthene > phenanthrene > pyrene > xylene > acenapthylene. Pearson correlation and principal component analysis (PCA) revealed the heavy metals were generated from automobile exhaust and parent rocks. Soil pollution index and Numerov composite pollution index revealed that the soil is safe, clean, and unpolluted with heavy metals. The mean levels of heavy metals were below the European Union (2006) permissible values for uncontaminated soil. The PAH mean values were within permissible standards for unpolluted agricultural, forest, and residential soils. The diagnostic ratios of PAHs, supported by PCA, showed that PAHs in soil were produced by pyrogenic and internal combustion of gasoline and kerosene. This method of soil contamination assessment by heavy metals and PAHs is invaluable for pollution assessors in Nigeria and another area in the world.